2000
DOI: 10.1046/j.1365-2222.2000.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetically engineered hypoallergenic rBet v 1 derivatives with rBet v 1 wild‐type by skin prick and intradermal testing: results obtained in a French population

Abstract: Genetically modified hypoallergenic derivatives of the major birch pollen allergen, Bet v 1 showed reduced capacity to induce immediate type skin reactions. They may represent candidate molecules for immunotherapy of birch pollen allergy with reduced risk of anaphylactic side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 32 publications
1
59
0
2
Order By: Relevance
“…Recently we produced by genetic engineering two recombinant fragments of Bet v 1 comprising aa 1-74 and aa 75-160 (26). The recombinant Bet v 1 fragments had lost their IgE binding capacity due to lack of their conformation and thus exhibited a Ͼ100-fold reduced allergenic activity when tested for their ability to elicit immediate skin reactions in patients (26,28,29). Although T cell epitopes of several Bet v 1-specific T cell clones seemed to be present on the rBet v 1 fragments (26), no information was available as to whether the derivatives would be capable of inducing significant lymphoproliferative responses in birch pollen-allergic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently we produced by genetic engineering two recombinant fragments of Bet v 1 comprising aa 1-74 and aa 75-160 (26). The recombinant Bet v 1 fragments had lost their IgE binding capacity due to lack of their conformation and thus exhibited a Ͼ100-fold reduced allergenic activity when tested for their ability to elicit immediate skin reactions in patients (26,28,29). Although T cell epitopes of several Bet v 1-specific T cell clones seemed to be present on the rBet v 1 fragments (26), no information was available as to whether the derivatives would be capable of inducing significant lymphoproliferative responses in birch pollen-allergic patients.…”
Section: Discussionmentioning
confidence: 99%
“…When we engineered two rBet v 1 fragments comprising aa 1-74 and aa 75-160, we found that the fragments, despite comprising the full Bet v 1 sequence, lacked IgE binding capacity due to a loss of their fold but induced proliferation of rBet v 1-specific T cell clones (26). Moreover, rBet v 1 fragments had a Ͼ100-fold reduced capacity to induce basophil histamine release and immediate type skin reactions in birch pollen allergic patients (26,28,29). Both rBet v 1 fragments also failed to induce eosinophil activation and late reactions in skin blisters of birch pollen-allergic patients (30).…”
mentioning
confidence: 99%
“…Patients received typically eight s.c. injections containing increasing doses (1,2,4,8,10,20,40, and 80 g of protein) of the trial preparations or placebo in one to two weekly intervals as a preseasonal treatment. Because of the strongly reduced allergenic activity of the recombinant allergen derivatives (16,17), maximal doses of 80 g of the active preparations per injection were tolerated by most of the patients. After reaching the maximal dose, the treatment was continued at four weekly intervals until the beginning of the flowering season.…”
Section: Methodsmentioning
confidence: 99%
“…In general, allergoids have demonstrated efficacy and safety profiles similar to those described for unmodified allergen extracts (90). In other studies, the introduction of point mutations or deletions has been used to reduce the number of conformational B cell epitopes displayed by an allergen (91). More recently, allergen has been coupled to synthetic bacterial DNA sequences (92).…”
Section: Figurementioning
confidence: 99%